Audiological Performance in Children with Inner Ear Malformations Before and After Cochlear Implantation: A Cohort Study of 274 Patients. (22nd September 2020) - Ozkan, Hilal Burcu; Cicek Cinar, Betul; Yucel, Esra; Sennaroglu, Gonca; Sennaroglu, Levent
Abstract: Background and Objective: Inner ear malformations (IEMs) are common in children with hearing loss. The different types of IEMs form a unique subgroup of cochlear implant (CI) candidates. We aimed to evaluate the auditory perception outcomes of CI in children with different types of IEMs and compare them with CI users without IEMs. Methods: The study included 274 CI users with and without IEMs as two groups (n = 137, each). Both groups' chronological age at implantation and duration of CI usage was matched (± 8 months). All subjects were evaluated pre‐operatively and post‐operatively by the Ling's sound test and the auditory perception test battery, which includes the Meaningful Auditory Integration Scale (MAIS), closed‐set Pattern Perception Test (PPT) and open‐set Sentence Recognition Test (SRT). Besides, children with IEMs were assessed for language development. Results: Progress in the IEMs' group differed according to the type of ear anomaly. CI users with enlarged vestibular aqueduct had the highest scores, while users with common cavity had the lowest. Children with IEMs performed well on the closed‐set test while having difficulty with the open‐set test. Conclusion: Cochlear implantation outcomes are favourable in IEMs' patients with a cochlear nerve visible on magnetic resonance imaging. Our results indicate that it is critical to take the anatomical differences into account during follow‐up and rehabilitation programmes. Each CI user should be evaluated according to his or her individual needs.